Determinants of poverty in elderly-headed households in the Philippines - Mapa, Dennis S.; Bersales, Lisa Grace S.; Albis, Manuel Leonard F.; Daquis, John Carlo P. (2011)
This paper looks at the impact of population dynamics on poverty in elderly-headed households in the Philippines using data from the Family Income and Expenditure Survey (FIES) from 2000 to 2006. The population of the elderly , or those 60 years and above. has increased from 3.2 million in 1990 to 4.6 million in 2000. This group is growing at a rate of 3.6% per annum and estimated to reach 7 million in 2010. Data from the FIES shows that the percentage of the elderly who are poor is increasing since 2003. Moreover, the percentage of elderly-headed household belonging to the poorest 10% of all households has been on the rise since 1997. An econometric model based on the logistic regression shows that the presence of a young dependent (aged 14 years old or below) increases the probability that the elderly-headed household will become poor by about 9 percentage points, controlling for other factors such as income of the household, education, age and gender of the household head, income transfer from abroad and regional-specific characteristics. The results of the econometric model suggest that the high proportion of young dependents create negative effects on the welfare of the elderly headed-household by increasing the probability of that household being poor. From the point of view of policy addressing the alarming poverty incidence in the country must include measures that will manage the country's bourgeoning population and bring down the fertility rate to a level that us conducive to higher income growth.
Keywords: Poverty; Older people